CONTRIBUTIONS OF CULTURAL DIVERSITY IN THE HISTORY OF PHYSICAL EDUCATION IN BRAZIL (Fiep Bulletin - online, 2013)
This research is an iconographic study of the quantity of the IRDEB, on the history of Brazilian the corporal culture afro. The filed historical inquiries as document in justinian codes, museums and houses of support to the culture, offer to the researchers and the community, data on the corporal culture, the sport, leisure and bahian physical education. The iconographic analyses of public archives are possibilities of contact with history contact through images on the bahian Culture, more specifically on the corporal culture afro-Brazilian, constituting a necessary field of inquiry for studies on the formation of the Brazilian society.
Keywords: history; physical education; cultural diversity